Clinical and genetic spectrum of a large cohort of patients with δ-sarcoglycan muscular dystrophy - Alonso-Pérez, Jorge; González-Quereda, Lidia; Bruno, Claudio; Panicucci, Chiara; Alavi, Afagh; Nafissi, Shahriar; Nilipour, Yalda; Zanoteli, Edmar; Isihi, Lucas Michielon de Augusto; Melegh, Béla; Hadzsiev, Kinga; Muelas, Nuria; et al. (Brain (London, England : 1878), 2022)
Sarcoglycanopathies include four subtypes of autosomal recessive limb-girdle muscular dystrophies (LGMDR3, LGMDR4, LGMDR5 and LGMDR6) that are caused, respectively, by mutations in the SGCA, SGCB, SGCG and SGCD genes. Delta-sarcoglycanopathy (LGMDR6) is the least frequent and is considered an ultra-rare disease. Our aim was to characterize the clinical and genetic spectrum of a large international cohort of LGMDR6 patients and to investigate whether or not genetic or protein expression data could predict a disease's severity. This is a retrospective study collecting demographic, genetic, clinical and histological data of patients with genetically confirmed LGMDR6 including protein expression data from muscle biopsies. We contacted 128 paediatric and adult neuromuscular units around the world that reviewed genetic data of patients with a clinical diagnosis of a neuromuscular disorder. We identified 30 patients with a confirmed diagnosis of LGMDR6 of which 23 patients were included in this study. Eighty-seven per cent of the patients had consanguineous parents. Ninety-one per cent of the patients were symptomatic at the time of the analysis. Proximal muscle weakness of the upper and lower limbs was the most common presenting symptom. Distal muscle weakness was observed early over the course of the disease in 56.5% of the patients. Cardiac involvement was reported in five patients (21.7%) and four patients (17.4%) required non-invasive ventilation. Sixty per cent of patients were wheelchair-bound since early teens (median age of 12.0 years). Patients with absent expression of the sarcoglycan complex on muscle biopsy had a significant earlier onset of symptoms and an earlier age of loss of ambulation compared to patients with residual protein expression. This study confirmed that delta-sarcoglycanopathy is an ultra-rare neuromuscular condition and described the clinical and molecular characteristics of the largest yet-reported collected cohort of patients. Our results showed that this is a very severe and quickly progressive disease characterized by generalized muscle weakness affecting predominantly proximal and distal muscles of the limbs. Similar to other forms of sarcoglycanopathies, the severity and rate of progressive weakness correlates inversely with the abundance of protein on muscle biopsy.